Preliminary evaluation of translated and culturally adapted internet-delivered cognitive therapy for social anxiety disorder: multicenter, single-arm trial in Japan - Yoshinaga, N; Thew, GR; Hayashi, Y; Matsuoka, J; Tanoue, H; Takanashi, R; Araki, M; Kanai, Y; Smith, A; Grant, SHL; Clark, DM (JMIR Publications, 2023)
Background: Internet-delivered cognitive therapy for social anxiety disorder (iCT-SAD), which is a therapist-guided modular web-based treatment, has shown strong efficacy and acceptability in English-language randomized controlled trials in the United Kingdom and Hong Kong. However, it is not yet known whether iCT-SAD can retain its efficacy following linguistic translation and cultural adaptation of treatment contents and implementation in other countries such as Japan.